Examining why undergraduate students do not seek membership of social greek organizations: a correlational studay at the University of Wisconsin - La Crosse - Zimmerman, Collin A. (My University, 2012)
This study explored why students are not joining social fraternities and sororities at the University of Wisconsin-La Crosse in larger numbers. A sample of 344 first semester college students responded to a 22-item online survey instrument. Based on responses, personal perceptions to likelihood of joining were analyzed along with involvement in student non-social Greek organizations. The survey concluded by exploring where respondents received their knowledge of social Greek organizations. The principal findings suggest students do not join social Greek organizations because they are unaware of their existence on campus. Implications for practice include that social Greek organizations must advertise their events to campus members. Current members must also learn about involvement oscillation for initiated members. Student affairs administrators, social Greek organization leaders and, social Greek organization advisors should learn how the stages of the Member Acquisition and Retention Model affect nonmembers and members.
Keywords: Universities and colleges United States; Education, Higher -- United States; Greek letter societies -- United States